EMOTIONAL INTERACTION ON BUYING DECISION, THE ROLE OF APPROPRIATE USEFULNESS AND ADIDAS RUNNING SHOE PRODUCT (AN EMPIRICAL STUDY IN JABODETABEK) - Ruslaini; Derren Christof Wilson; John Tampil Purba (Faculty of Economics and Business Universitas Pelita Harapan, 2025)
In globalization, the number of brands and products that have rivalry in the market has increased significantly, giving consumers many choices and alternatives of products and services to meet their wants and needs. Every brand and product must maintain Brand Familiarity, Intimacy, and Perceived Quality to increase repurchase intentions and generate emotional customer responses. This study aims to see the effect of Brand Familiarity, Intimacy, and Perceived Quality on purchase intentions. In addition, this study also wants to know the impact of purchase intentions on emotional responses to purchase intentions. The theory used is the Stimulus-Organism-Response (S-O-R) theory. This quantitative study uses questionnaires from respondents who are users of Adidas sports shoes from the running sports branch and who use Adidas brand sports shoes.